A study of basal stem rot disease in Bukit Lanchang, Melaka / ‘Arifah Nadhirah Ariff - Ariff, ‘Arifah Nadhirah (Faculty of Plantation and Agrotechnology, 2019)
Basal Stem Rot (BSR) disease caused by Ganoderma boninense is known to be as incurable disease since there is no known cure can treat this problem effectively. It mostly affects oil palm in matured stage. A study about Basal Stem Rot disease has been done in Bukit Lanchang, Melaka. This study was conducted in August 2018. Aim of this study is to determine the incidence and level of severity in the plantation area. It focused on soil factor that contributes to the disease incidence. Sample of the data had been taken in three different study areas. The physical appearance of fruiting body was examined by using Disease Index, MPOB. While the data regarding soil was obtained from Kompleks Pertanian Melaka. The soil types were determined by using Soil Textural Triangle. And the collected data was analyzed by using SPSS Statistics ver. 22. The result shown that Plot C had the lowest severity level which is 20.80%. Plot A and B disease severity’s level are 29.2% and 26.6% respectively. As for disease incidence, the Plot A had the highest incidence rate which was 25%, followed by Plot B at 15% and Plot C at 3%. There was significant difference between the incidence and level of severity in the plantation areas because the significance value (0.000) is less than P value (P<0.01). As a conclusion, Plot C had the lowest incidence and severity rate. This is due to high soil moisture in Plot C which affects the survival of the bacteria on the plantation area. This was supported by previous study which to determine rate of organism survivability on different soil moisture. Plot C had high soil moisture that help in lowering the survival rate of bacterial since the area is prone to flood due to the location of the plot near to the river.